Names and memories in Kiyovu, Kigali - Rosendal, Tove; Amini Ngabonziza, Jean de Dieu (University of Gothenburg, 2026)
The data contain texts, with transcriptions of recordings, conducted in the Kiyouvu and Nyamirambo areas of the Nyarugenge District in central Kigali, Rwanda, during the period 2022- 2024.

The data are provided by the researchers Jean de Dieu Amini Ngabonziza, University of Rwanda, and Tove Rosendal, University of Gothenburg.

Uploaded data contain 3 sets of datafiles:
• Transcriptions in Kinyarwanda of walk-along interviews with 30 participants
• Transcriptions in Kinyarwanda of 2 focus groups.
• Transcriptions with translations: Contains transcriptions in Kinyarwanda along with translations into English - side by side- of selected walk-along interviews and two focus group interviews.

‘Go-along interviews` (Kusenbach, 2003), often labelled walking interviews, were conducted and used to investigate local people’s reception of new street names introduced in 2012, how people navigate in the streets, and non-official naming of the urban environment. They also contain memories linked to the non-official names they use. The participants were asked to go to and stop at places where they knew old or present names or had memories tied to a street, a building or an area. This resulted in several short recordings of each participant, most of them targeting different streets and places.

Following the walking interviews, two focus group discussions were recorded: one with the group of older participants and one with the group of younger participants. The purpose of the discussions was to facilitate a more in-depth discussion of the participants' ideas, perceptions and feelings.

All recorded data were anonymized, transcribed and subsequently translated into English. As many recordings overlapped, the dataset Transcriptions with translations only contain selected, central recordings that were important for the research. The translations are focused on the content and are not annotated.

File folder naming conventions:
All data are pseudonymized, with a number- and letter system. However, it is possible to identify the age- and gender category of the interviewees from the file code: YF (Young woman), YM (Young man), OF (Old woman) and OM (Old man), added at the end of the pseudonymization code.

The dataset “Transcriptions in Kinyarwanda of walk-along interviews”:
This zipped folder contains walk-along interviews in the streets of Kigali with 30 participants, from 2 age groups: Young (below the age of 30) and older (older than 50).
The files in the folder are named with the pseudonymization code. In the transcriptions, which are in Kinyarwanda, there are indications in English about places/themes that the informant talks about in the left column, and also to the corresponding sound file, which is not deposited.

Dataset “Transcriptions in Kinyarwanda of focus group discussions”:
This dataset contains transcription in Kinyarwanda of focus group discussions: Focus group 1: Young (below the age of 30) and Focus group 2: old (older than 50).

The set “Transcriptions with translations”:
This set contains zipped files with transcriptions in Kinyarwanda and translations in English, totally 8 files: 6 files with transcriptions from walk-along interviews and 2 with transcriptions of focus group discussions (Focus group 1 with older participants and Focus group 2 with younger participants).

Data innehåller texter med transkriptioner av inspelningar som gjorts i områdena Kiyouvu och Nyamirambo i distriktet Nyarugenge i centrala Kigali, Rwanda, under perioden 2022–2024.
Uppgifterna tillhandahålls av forskarna Jean de Dieu Amini Ngabonziza, University of Rwanda, och Tove Rosendal, Göteborgs universitet.

Uppladdade data innehåller tre uppsättningar datafiler:
• Transkriptioner på kinyarwanda av intervjuer med 30 deltagare under promenader.
• Transkriptioner på kinyarwanda av två fokusgrupper.
• Transkriptioner med översättningar: Innehåller transkriptioner på kinyarwanda tillsammans med översättningar till engelska – sida vid sida – av utvalda intervjuer under promenader och två fokusgruppintervjuer.

”Go-along interviews” (Kusenbach, 2003), ofta kallade walk-along-intervjuer, genomfördes och användes för att undersöka lokalbefolkningens mottagande av de nya gatunamn som infördes 2012, hur människor navigerar på gatorna och icke-officiella namn på stadsmiljön. De innehåller också minnen kopplade till de inofficiella namn de använder. Deltagarna ombads att välja platser och stanna vid platser där de kände till gamla eller nuvarande namn eller hade minnen kopplade till en gata, en byggnad eller ett område. Detta resulterade i flera korta inspelningar av varje deltagare, varav de flesta handlade om olika gator och platser.

Efter walk-along-intervjuerna spelades två fokusgruppsdiskussioner in: en med gruppen äldre deltagare och en med gruppen yngre deltagare. Syftet med diskussionerna var att möjliggöra en mer ingående diskussion om deltagarnas idéer, uppfattningar och känslor.

All inspelad data anonymiserades, transkriberades och översattes därefter till engelska. Eftersom många inspelningar överlappade varandra innehåller datasetet ”Transcriptions with translations” endast utvalda, centrala inspelningar som var viktiga för forskningens huvudfokus. Översättningarna är inriktade på innehållet och är inte annoterade.

Namnkonventioner för filmappar:
Alla uppgifter är pseudonymiserade med ett system av siffror och bokstäver. Det är dock möjligt att identifiera ålders- och könskategorin för de intervjuade utifrån filkoden: YF (ung kvinna), YM (ung man), OF (äldre kvinna) och OM (äldre man), som läggs till i slutet av pseudonymiseringskoden.

Datasetet “Transcriptions in Kinyarwanda of walk-along interviews”:
Denna zippade mapp innehåller walk-along-intervjuer på gatorna i Kigali med 30 deltagare från två åldersgrupper: unga (under 30 år) och äldre (över 50 år).

Filerna i mappen är namngivna med pseudonymiseringskoden. I transkriptionerna, som är på kinyarwanda, finns referenser på engelska till platser/teman som informanten talar om i den vänstra kolumnen, samt till motsvarande ljudfil, som inte är deponerad.

Dataset “Transcriptions in Kinyarwanda of focus group discussions”:
Detta dataset innehåller transkriptioner på kinyarwanda av fokusgruppsdiskussioner: Fokusgrupp 1: Unga (under 30 år) och Fokusgrupp 2: Äldre (över 50 år).

Uppsättningen “Transcriptions with translations”:
Denna uppsättning innehåller zippade filer med transkriptioner på kinyarwanda och översättningar till engelska, totalt 8 filer: 6 filer med transkriptioner från walk-along-intervjuer och 2 med transkriptioner av fokusgruppsdiskussioner (fokusgrupp 1 med äldre deltagare och fokusgrupp 2 med yngre deltagare).
Namn och minnen i Kiyovu, Kigali
Keywords: SOCIAL RESEARCH; SAMHÄLLSFORSKNING; CHANGING SOCIETY; FÖRÄNDERLIGT SAMHÄLLE; COMMUNITY BEHAVIOUR; SAMHÄLLSDELTAGANDE; URBAN DEVELOPMENT; STADSUTVECKLING; LANGUAGE POLICY; SPRÅKPOLITIK; PREDOMINANT LANGUAGES; DOMINERANDE SPRÅK; LANGUAGE DISCRIMINATION; SPRÅKDISKRIMINERING; MEMORY; MINNE; OFFICIAL LANGUAGES; OFFICIELLA SPRÅK; RESEARCH METHODOLOGY; FORSKNINGSMETODOLOGI; Language and linguistics; Språk och lingvistik; Political ideology; Politisk ideologi; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Cultural and national identity; Kulturell och nationell identitet; Community, urban and rural life; Lokalsamhälle, stads- och landsbygdsliv; Social change; Social förändring; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Development Studies; Utvecklingsstudier